Combination of Platelet-rich Fibrin (PRF) in Advanced Periodontitis Stage Treatment - Harsas, Nadhia Anindhita; Tadjoedin, Fatimah Maria; Sulijaya, Benso; Hutomo, Dimas Ilham; Purba, Melinda Rabekka; Sasri, Cahyaning Wulan (Journal of Indonesian Dental Association, 2023)
Introduction: The treatment of advanced periodontitis has been a challenge for clinicians. Platelet-rich fibrin (PRF) is a second-generation platelet concentrate that contains various growth factorss and cytokines that promote tissue regeneration. The use of PRF in combination with other regenerative materials and techniques has been shown to be effective in the treatment of intrabony defects. This case series aims to evaluate the efficacy of PRF combinations in the regenerative treatment of patients with advanced periodontitis. Case report: Two patients diagnosed with advanced periodontitis (stage III/IV grade C) were selected for this study. After the completion of periodontal initial therapy, there were still pockets with a probing depth ≥ 5 mm (5–10 mm). Therefore, surgical interventions were planned. The first case used the combination of PRF with bone graft and guided tissue regeneration (GTR), while open flap debridement (OFD) with the addition of PRF and bone graft to create sticky bone was done in the second case. Three to five months of follow-up showed favorable outcomes, as evidenced by reductions in probing depth (PD), gains in clinical attachment level, and filling of bone defects, as well as improvements in patient comfort and rapid wound healing. Conclusion: The combination of PRF with grafting material and/or GTR has been shown to be a beneficial therapeutic approach for periodontal regenerative therapy. Platelet-rich fibrin in periodontal surgery may accelerate the tissue healing process.